The Role of Time Management and Sleep Quality on the Well-Being of Working Students - Saputra, Cherry Violin; Rostiana, Rostiana; Hindradjat, Juliana (GLOBAL HEALTH SCIENCE GROUP, 2023)
Balancing work and studies is a challenging thing to do, especially for university students. It is crucial for working students to focus on their well-being, which plays a major key role in personal growth. In order to achieve and maintain one’s well-being, effective time management and good quality of sleep are essential. These aspects can be difficult for working students due to time constraints, as working students are said to have difficulties in managing their schedule and tend to have inadequate rest. The aim of this study is to explore how time management and sleep quality affect the well-being of working students. This study employed a non-experimental correlational quantitative research design. Convenience sampling was used in this study with a sample size of 251 students from universities across Indonesia. The instruments used in this study include Time Management Questionnaire (Britton & Tesser, 1991), Pittsburgh Sleep Quality Index (Buysse, 1989), and WHO-5 Well-being Index (WHO, 1998). Non-experimental correlational approach is used in this study with a total of 251 participants. Validity and reliability assessments were conducted on the research instruments, with all three of them achieving good reliability, indicated by a Cronbach's alpha exceeding 0.06. The data were analyzed using SPSS version 25 with the multiple linear regression method. The descriptive analysis in this study indicates that participants' overall well-being is low, averaging at 1.958. This study found a significant p-value (0.000 < 0.05), signifying that well-being is influenced by time management and sleep quality. The R-squared value of 0.502 suggests that 50.2% of well-being variability is explained by these factors. The concurrent influence of time management and sleep quality predicts well-being, with higher levels in both corresponding to increased well-being.